2020
DOI: 10.1590/0034-761220200354
|View full text |Cite
|
Sign up to set email alerts
|

Combate à COVID-19 sob o federalismo bolsonarista: um caso de descoordenação intergovernamental

Abstract: Resumo Este artigo analisa como o federalismo brasileiro tem afetado o combate à COVID-19. Tendo por base uma análise histórico-institucional do caso brasileiro, busca-se compreender como o modelo federativo construído pelo governo Bolsonaro influenciou as respostas ao combate da pandemia no país, bem como os resultados do confronto de dois modelos federativos nesse processo. De um lado, o ideário e as estruturas institucionais da Constituição de 1988 com características cooperativas e forte coordenação federa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
86

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(128 citation statements)
references
References 8 publications
1
41
0
86
Order By: Relevance
“…As one of the world's most populous democracies encompassing roughly half of South America, the COVID pandemic struck Brazil, a country with over 200 million inhabitants, as it continued to face political and economic duress stemming from the aftermath of a protracted regression that began in 2014 (Barbosa, 2017) and political polarization stemming from the impeachment of president Dilma Rouseff in 2016 and the election of Jair Bolsonaro in 2018 (Abrucio, Grin, Franzese, Segatto & Couto, 2020). In this context, the risks posed by the coronavirus were especially high for millions of people who live in poverty or have only recently emerged from it and due to the limited infrastructure that exists for those requiring hospital care (Rache et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As one of the world's most populous democracies encompassing roughly half of South America, the COVID pandemic struck Brazil, a country with over 200 million inhabitants, as it continued to face political and economic duress stemming from the aftermath of a protracted regression that began in 2014 (Barbosa, 2017) and political polarization stemming from the impeachment of president Dilma Rouseff in 2016 and the election of Jair Bolsonaro in 2018 (Abrucio, Grin, Franzese, Segatto & Couto, 2020). In this context, the risks posed by the coronavirus were especially high for millions of people who live in poverty or have only recently emerged from it and due to the limited infrastructure that exists for those requiring hospital care (Rache et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The Brazilian case clearly demonstrates a high level of ambiguity during the pandemic, partly owing to the unprecedented nature of the situation but also accentuated by the absence of intergovernmental coordination (ABRUCIO et al, 2020;TAVARES;SILVEIRA;PAES-SOUSA, 2020). Although over recent decades the Brazilian state has strengthened its capacity to design integrated and coordinated federative interventions, the crisis has shown that it is not sufficient in the absence of leadership (ABRUCIO et al, 2020). Thus, despite the existence of national public policy systems, such as SUS and SUAS, federative cooperation and collaboration does not happen without deliberate decision-making by public officials, especially when the beliefs, interests and logics of political action conflict with or diverge from these systems.…”
Section: Discussion: the Centralization Of Decision-making Processes Conflicts And Ambiguitiesmentioning
confidence: 99%
“…The second is the feeling of increased risk and suffering among professionals, who find themselves in extreme, even life or death, situations and are directly exposed to infection, intensifying their sense of insecurity (KHANAL et al, 2020). Such feelings can be intensified in contexts of political conflict and lack of inter-agency coordination, as in the Brazilian case (ABRUCIO et al, 2020), resulting in increased uncertainty about how best to simultaneously provide the public with adequate care and ensure the safety of frontline workers.…”
Section: Street Level Bureaucracy: From Routine To Emergencymentioning
confidence: 99%
“…A coordenação é entendida como atividades de dois ou mais parceiros que querem se desenvolver e, para isso, mobilizam recursos, ajuda mútua ou harmonizam as suas políticas, programas, procedimentos e práticas, de modo a maximizar a eficácia dos recursos empregados (TRENTIN, 2016). Contribui ainda, para compartilhar objetivos, de modo a reduzir duplicação e sobreposição (BAKVIS, JUILLET, 2004) e, assim, desigualdades territoriais (ABRUCIO et. al, 2020).…”
Section: Políticas Públicas No Turismo E a Pandemia Decorrente Do Sarunclassified
“…A coordenação intergovernamental que foi construída está posta à prova. Nesse cenário, os governos subnacionais reafirmaram a coordenação horizontal diante da coordenação federal (ABRUCIO et al, 2020) nas ações para enfrentamento de COVID-19 e do turismo.…”
Section: Considerações Finaisunclassified